[Arkusz znaczków podziemnych ze znanymi opozycjonistami] . Sheet of unofficial stamps with popular dissidents - Poczta Solidarność. (Poczta Solidarność)
Brown print on white paper without perforation. Sheet of stamps with "Poczta Solidarność" imprint and "Fighting Solidarity" symbol, represents known figures of the Polish democratic opposition: Z. Romaszewski, M. Jurczyk, H. Bujak, J. Rulewski, A. Rozpłochowski, A. Michnik, S. Jaworski, K. Modzelewski, J. Kuroń, A. Gwiazda, G. Pałka. Price: 20 zł per stamp.